¿De quién es la falta de ética del mayor o del iniciado? - Borges Bartutis, María Vicenta (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The objective of this paper is to illustrate the current reality of the Ocha-Ifá Rule in Cuba, which is characterized by the diversity mediated by modernity, which together with other social factors and syncretism identifies a social problem originated, in principle, by the circumstance in which the Spanish white man arrived in Cuba, the way in which he brought the African black and the conditions in which he kept him enslaved; nevertheless, the new reality, black, with skill and wisdom preserves and protects their traditions, their culture. Thus, the expansion of the primary oral transmission of African culture begins in the process of “transculturation”; At present, despite the survival of this religious practice, the modern trend has changed the coexistence between the branches and the actions of practitioners, who with the intention of making their actions prevail, set excessive prices for the established ritual ceremonies. Or they constantly violate duties and rights, thus deforming what is stipulated in the Ocha-Ifá Rule. The above is the result of the «boom» of the Ocha-Ifá Rule «Santería»; event that, sometimes for some implies a fashion and for others the spirituality of the practitioner, which differs from the ethics, respect and confidence of the believer in his practice, therefore the contrast in Cuba between the historical moment is questioned lived by those who preceded us; the silent, discreet scenario in which, for various reasons, they guarded the religion and the current context in which the Ocha-Ifá Rule is practiced.